Pelatihan Pembuatan Mi Ayam Organik dari Ubi Ungu kepada KWT Madani di Twelves Organic, Claket, Mojokerto - Putri Aeni Erviyanti; Dita Atasa (Jurnal Nusantara Berbakti, 2023)
Sweet potato is a food crop that is high in carbohydrates. Many people still consume sweet potatoes in their whole form, such as steamed, boiled, baked, or even fried. In fact, sweet potatoes can be processed into high-value products, such as sweet potato noodles. The training was conducted by UPN “Veteran” East Java students to the women of the Madani farmer women's group as a form of community service. The purpose of this community service activity is to increase the added value of organic purple sweet potato commodities into chicken noodles at Twelve's Organic. The methods used are lectures, practice, and evaluation. The training activities and results went well and smoothly. This can be seen from the active participants who participated in the training event according to the timeline that had been made, as well as the discussions during the training.